Hubungan Luas Lahan Dan Tingkat Pendidikan Dengan Peningkatan Pendapatan Usahatani Padi Di Desa Topore Kecamatan Papalang - Sulaiman, S; Rasmahwati, R (Agrifo : Jurnal Agribisnis Universitas Malikussaleh, 2018)
This research intent for example to : 1) Knowing relationship among farm extent with paddy farming revenue enhancement, and 2) Knowing relationship among level education with paddy farming revenue enhancement. Meanwhile this research utility is 1) As material as information for farmer deeping to bring off paddy farming, 2) Can be consideration divide policy take in arrange program that concern farmer revenue enhancement effort, and 3) Literature material for further researcher. This research was performed at Topore Village Papalang district Mamuju Regency, on august until September 2017. Topore silvan elect as region of research at goes upon on that judgment Topore Village constitutes one of village which have acreage of rice filed extent that enough extensive. Population in observational is all paddy farmer that gets location at Silvan Topore Papalang district Mamuju Regency. Meanwhile sample in observational it is chosen at Simple Random Sampling with farmer amount as much 432 person taken by respondents as big as 10 percents which is as much 43 respondents. Result observationaling to point out that : Far ranging ala ascendant farm signifikan to paddy farming revenue enhancement which is as big as 84,7 percents, meanwhile Zoom education not signifikan's ala ascendant to paddy farming revenue enhancement which is just as big as 0,7 percents.